Phoretic Poecilochirus mites specialize on their burying beetle hosts. Issue 24 (7th November 2017) - Nehring, Volker; Müller, Josef K.; Steinmetz, Nadine
Abstract: Recurring species interactions can cause species to adapt to each other. Specialization will increase the fitness of symbionts in the coevolved association but may reduce the flexibility of symbiont choice as it will often decrease fitness in interactions with other than the main symbiont species. We analyzed the fitness interactions between a complex of two cryptic mite species and their sympatric burying beetle hosts in a European population. Poecilochirus mites (Mesostigmata, Parasitidae) are phoretic on burying beetles and reproduce alongside beetles, while these care for their offspring at vertebrate carcasses. While Poecilochirus carabi is typically found on Nicrophorus vespilloides beetles, P. necrophori is associated with N. vespillo . It has long been known that the mites discriminate between the two beetle species, but the fitness consequences of this choice remained unknown. We experimentally associated both mite species with both beetle species and found that mite fitness suffered when mites reproduced alongside a nonpreferred host. In turn, there is evidence that one of the beetle species is better able to cope with the mite species they are typically associated with. The overall fitness effect of mites on beetles was negative in our laboratory experiments. The Poecilochirus mites studied here are thus specialized competitors or parasites of burying beetles. Abstract : We experimentally associated two Poecilochirus mite species with two sympatric burying beetle species and found that mite fitness suffered when mites reproduced alongside a nonpreferred host. In turn, there is evidence that one of the beetle species is better able to cope with the mite species they are typically associated with. The overall fitness effect of mites on beetles was negative in our laboratory experiments. The Poecilochirus mites studied here are thus specialized competitors or parasites of burying beetles.